Radicular cyst in primary dentition showing angiolymphoid hyperplasia with eosinophilia (ALHE)-like features: An immunohistochemical study - Bertasso, Amanda Silva; Nelson-Filho, Paulo; da-Silva, Raquel Assed Bezerra; dos-Santos, Maria Cecília Gorita; Javaroni, Julia Biliato; Silveira, Heitor Albergoni; León, Jorge Esquiche (Journal of Oral Diagnosis, 2023)
The microscopical diagnosis of radicular cyst (RC) is straightforward; nonetheless, in some cases with unusual histopathological features, strict clinicopathological correlation is necessary to achieve the correct diagnosis. We report a case of a 5-year-old girl was referred presenting extensive carious lesion in the tooth #55, associated with vestibular sinus tract. Medical history revealed allergic asthma diagnosis. After clinical and imaginological exams, the deciduous tooth was extracted. Microscopically, the soft tissue lesion attached to the root showed typical RC features; however, in the cystic capsule, lymphoid follicles and vascular networks (lined by epithelioid endothelial cells) surrounded by numerous eosinophils, were observed. Immunohistochemistry, through CD3, CD20, CD34 and alpha-smooth muscle actin antibodies, highlighted these findings. Moreover, CD1a and CD207 were negative. To the best of our knowledge, this is the first report of RC showing angiolymphoid hyperplasia with eosinophilia (ALHE)-like features.